2022
DOI: 10.3390/ijms23158458
|View full text |Cite
|
Sign up to set email alerts
|

The Kv10.1 Channel: A Promising Target in Cancer

Abstract: Carcinogenesis is a multistage process involving the dysregulation of multiple genes, proteins, and pathways that make any normal cell acquire a cancer cell phenotype. Therefore, it is no surprise that numerous ion channels could be involved in this process. Since their discovery and subsequent cloning, ion channels have been established as therapeutic targets in excitable cell pathologies (e.g., cardiac arrhythmias or epilepsy); however, their involvement in non-excitable cell pathologies is relatively recent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 114 publications
0
2
0
Order By: Relevance
“…Considering potential therapeutic strategies, it could be interesting to combine the use of AA9 with inhibitors of the Kv10.1 channel, known to regulate cell cycle [61], drug resistance and tumor progression [91], some of which have already been proposed for clinical applications [78]. In particular, it will be interesting to analyze the effectiveness of the potential synergistic action of TG2 inhibitors and astemizole which are known to work in combination with other drugs [92,93] which in this case would also have the same target, the Kv10.1 channel [94].…”
Section: Discussionmentioning
confidence: 99%
“…Considering potential therapeutic strategies, it could be interesting to combine the use of AA9 with inhibitors of the Kv10.1 channel, known to regulate cell cycle [61], drug resistance and tumor progression [91], some of which have already been proposed for clinical applications [78]. In particular, it will be interesting to analyze the effectiveness of the potential synergistic action of TG2 inhibitors and astemizole which are known to work in combination with other drugs [92,93] which in this case would also have the same target, the Kv10.1 channel [94].…”
Section: Discussionmentioning
confidence: 99%
“…Kv10.1 belong to the superfamily of voltage-gated potassium channels and is assembled as homotetramers ( Whicher and MacKinnon, 2016 ). Diverse authors have shown an overexpression of Kv10.1 in cancer samples, contrasting with a low expression in healthy tissues ( Farias et al, 2004 ; Hemmerlein et al, 2006 ; Ortiz et al, 2011 ; Martínez et al, 2015 ; Luis et al, 2022a ). Also, it has been described that Kv10.1 overexpression is associated with increased cell proliferation, angiogenesis, and chemo- and radio-resistance phenotype ( Pardo et al, 1999 ; Downie et al, 2008 ; Bai et al, 2013 ; Luis et al, 2022b ).…”
Section: Introductionmentioning
confidence: 99%